TOWARDS FACING GLOBAL FAMINE: MODELING FOOD DISTRIBUTION ACCORDING TO IRAQI CASE - Saleh, Mohammed Mahdi (European Scientific Journal, ESJ, 2015)
The total population facing malnutrition and hunger is about one billion at the global level. As the global population increases from 7.3 billion in 2015 to 9.2 billion in 2050, the total new population that needs to be fed until 2050 is 2 billion. This was in addition to the one billion people facing starvation. Additional food products should be combined together to feed an additional population of three billions in thirty five years to come. Due to the constraint of agricultural land and food production deficit to meet the food security standard of a population of more than nine billion, global famine is expected to prevail unless hard work is done at both the national and the international scales in two dimensions under the help of the United Nations (FAO, WFP, and UNICAFE). The first dimension is increasing total food output to meet the need of all the people for a healthy and active food requirements. In the second dimension which is due to the wide discrepancies of income distribution between countries and within countries, it is necessary to adopt subsidized food distribution system at the national scale for countries where their population largely or partially cannot afford to obtain the required food at all time. The core of this paper is the second dimension with reference to Iraqi food distribution system adopted during thirteen years of comprehensive sanction, and it was proven to be successful in saving Iraqi people from famine. It was mentioned that the public food distribution which was recently adopted in India covers 800 million persons. This paper proposed guidelines for building infrastructure like silos and large warehouses for strategic reserve to secure the flow of food. This has to be facilitated by preparing transport network to carry food from ports or local farmers to silos and warehouses, and to deliver food through network of private retailers so that beneficiaries can obtain food from their residential areas. National aid is required for counties facing malnutrition and starvation.